Pemerolehan Bahasa dan Belajar Bahasa Menurut Pandangan Konvergensi - Sabekti, C. A (Jurnal Pendidikan, 2009)
Two different views state that oneâs intelligent growth is determined by genetic factor by a learning factor . This controversial has been known for a long time. Nowadays, it is said that intelligent growth is determined by both nature and nurture. This is a convergence theory.Whole language is a theory of learning which is rooted fromÂ convergence view. It consists of not only psycholinguistics and sociolinguistics aspects but also language acquisition and language learning. Learning a language is based on these four principles : Learning Theory, The Nature of Language, The Nature of Language Learning and Curriculum. Whole Language is in line with those mentioned above.